GIS-Based USLE Assessment of Land Use Change Impacts on Erosion and Streamflow in the Ciujung Watershed - Agung Satria Kurniawan; Dyah Indriana Kusumastuti; Endro Prasetyo Wahono; Ofik Taufik Purwadi; Ahmad Zakaria (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study investigates the impact of land use change on streamflow discharge and soil erosion in the Ciujung Watershed, Indonesia. The research aims to evaluate hydrological responses and erosion dynamics associated with changes in land cover between 2016 and 2021. Rainfall and discharge analyses were conducted using the Thiessen Polygon method and statistical regression analysis, while erosion was estimated using the Geographic Information System (GIS)-based Universal Soil Loss Equation (USLE). Land use changes were identified through Landsat image interpretation. The results indicate that increased rainfall and substantial land use conversion have altered watershed conditions. Forest, shrubland, swamp, and paddy field areas decreased, while plantation, dryland farming, and settlement areas expanded significantly. These changes were associated with increases in annual flow volume, average discharge, runoff coefficient, erosion rate, and sediment yield, indicating a decline in watershed performance. Regression analysis revealed a strong positive relationship between rainfall and river discharge variables. The GIS-based USLE analysis showed a substantial increase in erosion and sediment production during the study period. The findings demonstrate that land use change, combined with increasing rainfall, has accelerated watershed degradation and heightened erosion risks in the Ciujung Watershed. Sustainable land management and conservation measures are therefore essential to mitigate future environmental impacts and maintain watershed functions.